Consumables Inventory Management in The Pharmacy Installation of PT Siloam Internasional Hospitals Manado - Lopis, Rolla Amelia Claudia; Mandey, Silvya L.; Pondaag, Jessy J. (Yayasan Abdurrauf Cendekia Nusantara, 2025)
This research aims to determine the correct implementation of inventory management analysis using the Always Better Control (ABC), Lead Time, Safety Stock, and Re-Order Point methods, whether they are in accordance with the current inventory management process which is running in a systematic manner. This research is a type of quantitative research with a descriptive approach where this research uses secondary data sources, the Time Series data collection method was collected using the documentation method with a Purposive Sampling Technique research sample from a total of 3068 consumables at the PT Siloam International Hospitals Manado Pharmacy Installation in the author's research using a time series data approach with a time span of 3 months from January-March 2025. Analysis of Always Better Control (ABC), Lead Time, Safety Stock, and Re-Order Point is better implemented to optimize stock inventory. There is potential for stock vacancies and service delays which result in reduced consumer confidence, inconvenience due to delays in service resulting from delays in fulfilling supplies of consumables from the Pharmacy Installation warehouse for the sustainability of the hospital's credibility in the hope of optimizing the inventory of Consumables Inventory according to the analysis calculations that have been carried out to secure stock, make shopping plans and collaborate with third parties (Suppliers).